(untitled) (Research, Society and Development, 2021)
This study aimed at evaluating the reproductive performance of 42 primiparous crossbred Angus cows at 24-25 months of age fed or not a supplement at 0.8% of body weight. The supplement, with 14% crude protein and 70% total digestible nutrients, was supplied for 30 days pre-mating, during the transition period from cultivated to natural pastures, consisting of 23 days on oats (Avena strigosa Schreb) and ryegrass (Lolium multiflorum Lam.), and seven days on natural pasture. A continuous grazing method was applied, with average forage offer of 1450 and 2150 kg dry matter/ha for the cultivated and the natural pasture, respectively. The cows were distributed in a completely randomized design in a non-supplemented (control) and a supplemented group according to weight, body condition score, and calving date. Cow and calf body development was evaluated from the beginning of supplementation period and pregnancy diagnosis. Supplementation did not influence final body weight and body condition score of the cows (P >0.05). However, average daily gain of the supplemented cows and their calves (0.465 and 0.829 kg, respectively) was higher (P <0.05) than that of non-supplemented cows (0.227 and 0.644 kg, respectively), resulting in higher calf weaning weight at five months of age (130.9 vs. 117.3 kg, respectively). The supplemented cows showed higher pregnancy rate already on day 42 of pregnancy (80.9 vs. 28.6%), as well as on day 63 (80.9% vs. 57.1%) compared with non-supplemented cows. Primiparous cows at 24-25 months of age and that conceive have higher body weight and body condition score at the beginning of breeding season.